Alcohol Availability Restriction Policy and Changes in Consumer Behavior in Lithuania in 2016–2019 - Karpuškienė, Vita (Ekonomika, 2021)
To reduce alcohol consumption, in 2018 the Lithuanian Government introduced new restrictions on alcohol sales time, consumer age, and alcohol advertising. These restrictions apply to the entire population, regardless of alcohol consumption behavior. Such actions of the government were provoked by the scale of the problem; according to the data provided by the World Health Organization and the European Union Commission, Lithuania sits among the leading countries in alcohol consumption. The policies taken by the government to reduce alcohol consumption are described by many economists as paternalistic, as they reduce an individual’s freedom of decision. The aim of this paper is to evaluate the changes in alcohol consumption behavior after the regulatory measures entered into force and the public attitude towards these measures based on research results. This article presents the results of a study first conducted in December 2016 by the researchers of the Faculty of Economics of Vilnius University and the representatives of the Lithuanian Business Confederation*. The aim of the study was to distinguish the different groups of alcohol consumers and their alcohol consumption behavior and attitudes towards the alcohol restriction policies.** To achieve this aim, an analysis of scientific papers, a population survey, and statistical analysis methods were used. The authors conclude that alcohol restriction policies, met with a relatively favorable public attitude, may have adjusted levels of alcohol consumption and its patterns, but the increase in the number of young people among alcohol consumers is not in line with the expected policy outcomes. The measures adopted did not encourage respondents to give up alcohol in the longer term (12 months).